The activity of the RGA5 sensor NLR from rice requires binding of its integrated HMA domain to effectors but not HMA domain self‐interaction. (29th June 2022) - Xi, Yuxuan; Chalvon, Véronique; Padilla, André; Cesari, Stella; Kroj, Thomas
Abstract: The rice nucleotide‐binding (NB) and leucine‐rich repeat (LRR) domain immune receptors (NLRs) RGA4 and RGA5 form a helper NLR/sensor NLR (hNLR/sNLR) pair that specifically recognizes the effectors AVR‐Pia and AVR1‐CO39 from the blast fungus Magnaporthe oryzae. While RGA4 contains only canonical NLR domains, RGA5 has an additional unconventional heavy metal‐associated (HMA) domain integrated after its LRR domain. This RGA5HMA domain binds the effectors and is crucial for their recognition. Investigation of the three‐dimensional structure of the AVR1‐CO39/RGA5HMA complex by X‐ray crystallography identified a candidate surface for effector binding in the HMA domain and showed that the HMA domain self‐interacts in the absence of effector through the same surface. Here, we investigated the relevance of this HMA homodimerization for RGA5 function and the role of the RGA5HMA effector‐binding and self‐interaction surface in effector recognition. By analysing structure‐informed point mutations in the RGA5HMA ‐binding surface in protein interaction studies and in Nicotiana benthamiana cell death assays, we found that HMA self‐interaction does not contribute to RGA5 function. However, the effector‐binding surface of RGA5HMA identified by X‐ray crystallography is crucial for both in vitro and in vivo effector binding as well as effector recognition. These results support the current hypothesis that noncanonical integrated domains of NLRs act primarily as effector traps and deepen our understanding of the sNLRs' function within NLR pairs. Abstract : Mutant analysis validates the effector‐binding surface in the noncanonical integrated HMA domain of the rice immune receptor RGA5 and shows that its self‐interaction does not contribute to RGA5 function.